10F-12F Architectural finishes (RFA-425_Rev A) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture (BUCG-ABC JV); Web Structures (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.